Pemberdayaan komunitas peduli lingkungan melalui PKM Kubermas tahap 1 di Universitas Khairun - Abdul Rasyid Tolangara; Sundari Sundari; Abdu Mas'ud (Universitas Hamzanwadi, 2021)
Kubermas (Community Work Lecture) is one of the intracurricular programs organized by Khairn University. The form of activity is in the form of service activities to implement the Tri Dharma of Higher Education. In phase 1, the main program of this Kubermas PKM activity is community empowerment to carry out the conservation of spices and herbs in home gardens. The activity location is on Campus 1 of FKIP, Akehuda sub-district, North Ternate city, and RT 14, Kayu Merah sub-district, South Ternate city. The objectives of the Kubermas PKM are 1) to form a community of people who have the sensitivity to plant and care for and utilize herbs and spices in the yard of the house as a conservation effort; 2) provide direct experience to students participating in Kubermas in community empowerment programs at Kubermas locations. The method of service is community participation and training. The results of this community service are public knowledge about the conservation of home garden spices and herbs and knowledge of the use of home garden spices and herbs in the manufacture of Hand Sanitizermade from herbs and Rorano during the pandemic. Students have direct experience of community assistance methods and the use of home gardens